Breakdown Characteristic of Palm and Coconut Oil with Different Moisture - N. A. M.Jamail; N. A. Azali; E. Sulaiman; Q.E. Kamarudin; S.M.N.S. Othman; M.S. Kamarudin (Institute of Advanced Engineering and Science, 2018)
Oils acts as insulation and cooling agent in the transformer. Petroleum-based oils are widely used in transformers due to their qualified properties as good insulation materials. Unfortunately, the used of petroleum-based oils has adverse effects on environment in the event of any failure to transformers such as tank leakage or explosions. Therefore, researchers have been studied and have found environmentally friendly oil that is suitable as substitutes in transformer. Thus, breakdown voltage tests using direct current and alternating current with the addition of different water content were performed to identify the potential of palm oil and coconut oil in the transformer isolation system. Refined, Bleached and Deodorized oil (RBDPO) and coconut oil samples were selected to be test in this study. The oil samples were test by varies the gap distance of test cell electrode and the level of water content. As a conclusion, RBDPO oil has greater breakdown voltage test under DC breakdown voltage test in term of increment of the gap distance.